Radikalisme Agama Penghambat Kemajuan Peradaban - Arif Nuh Safri (UIN Sunan Kalijaga Yogyakarta, 2013)
Exclusivism in religion is one factor that is closely related to the emergence of religious radicalism or violence. Exclusivity is also of course a poor indicator of human civilization caused by social empathy is still thin. Thus, it is clear that such a religious pattern is built with an exclusive insight anyway. Through this article, the author would like to express that violence in any form is a major obstacle in achieving an advanced civilization, or at least reach back civilization achieved by the Prophet as a carrier Muhammmad treatise. In addition, this article also emphasizes that Islam is not a religion that teaches violence exclusively.